21-3(4x-5)=9x-57

Simple and best practice solution for 21-3(4x-5)=9x-57 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 21-3(4x-5)=9x-57 equation:


Simplifying
21 + -3(4x + -5) = 9x + -57

Reorder the terms:
21 + -3(-5 + 4x) = 9x + -57
21 + (-5 * -3 + 4x * -3) = 9x + -57
21 + (15 + -12x) = 9x + -57

Combine like terms: 21 + 15 = 36
36 + -12x = 9x + -57

Reorder the terms:
36 + -12x = -57 + 9x

Solving
36 + -12x = -57 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
36 + -12x + -9x = -57 + 9x + -9x

Combine like terms: -12x + -9x = -21x
36 + -21x = -57 + 9x + -9x

Combine like terms: 9x + -9x = 0
36 + -21x = -57 + 0
36 + -21x = -57

Add '-36' to each side of the equation.
36 + -36 + -21x = -57 + -36

Combine like terms: 36 + -36 = 0
0 + -21x = -57 + -36
-21x = -57 + -36

Combine like terms: -57 + -36 = -93
-21x = -93

Divide each side by '-21'.
x = 4.428571429

Simplifying
x = 4.428571429

See similar equations:

| 4(x+3)+2=50 | | 4x+36-7x-56=83 | | 3(r-2)=24 | | 20+17w=-6+15 | | 3(2x-5)+8x-6=x/2-(5x+3) | | 7(9+15e)+19-49e+70+10e=88 | | 7(9+15e)+19-49e+70+10e=90 | | 20+17w=6+15w | | 7(9+15e)+19-49e+70+10e=91 | | -0.5+2y=-1 | | 7(9+15e)+19-49e+70+10e=98 | | 3(x+6)=81x | | -540.00+13.5g=4158.00 | | 3r-21=7 | | -540.00+13.5g=1500.00 | | 4x+121=2x+123 | | 6d-10= | | 17(t-3)(t-8)=0 | | 15.4+3.5h=1.2h-6 | | 3.3n+3.4=54+6n | | 12d-84= | | -6+15g=9+15g | | 8y-30=34 | | 3(y+2)=y+24 | | 2x+15=14-x | | (-8x+2y)(-4x+4y)= | | c=(3x+y-4)*5-5y+3 | | 5-15t=-15t-14 | | 4+14x=2x-8+12x | | -18n+6n-3=5-12n | | 965.3616=87.92*r^2+62.17*r | | -6y-1=-9y+2 |

Equations solver categories